The effect of high voltage galvanic stimulation on quadriceps femoris muscle strength knee osteoarthritis [Di̇z osteoartri̇ti̇nde yüksek voltaj galvani̇k sti̇mülasyonun kuadri̇seps femori̇s kas gücüne etki̇si̇] - (:unkn) unknown (My University, 2003)
Pain and limitation of range of motion are the most prominent symptoms of knee osteoarthritis being responsible for the weakness of the quadriceps muscle. The aim of this study is to investigate the effect of high voltage galvanic stimulation (HVGS) on strengthening the quadriceps femoris muscle in patients with knee osteoarthritis. Twenty-four female patients were enrolled in the study and were divided into two groups. In the 6-week study period the HVGS group were given conventional rehabilitation program (electrotherapy, quadriceps femoris isometric exercises) and an additional application of HVGS. The control group received conventional rehabilitation program only. The patients were evaluated at the beginning and at the end of the study with isokinetic testing, magnetic resonance imaging, visual analogue scale, face scale, SF36 and 50 meter walking time. The only significant parameter in the HVGS group compared to the control group was the increase of quadriceps muscle strength in 0° knee extension. HVGS did not differ from conventional rehabilitation program in the analgesic effect and on the functional level of the patients. In conclusion, conventional rehabilitation program was found effective on the treatment of knee osteoarthntis, and the application of additional HVGS in different degrees of knee flexion for more than six weeks could be beneficial to increase the strength of the quadriceps femoris muscle.
Keywords: High voltage galvanic stimulation; Knee osteoarthritis; Muscle strengthening; Rehabilitation